(untitled) (Journal of Paediatric Surgeons of Bangladesh, 2016)
Introduction: Myelomeningocele is a single most common congenital malformation that affects the entire central nervous system and because of extensive internal CNS involvement, its management remains controversial. Proper management of affected children can lead to a meaningful and productive life, and poorly managed cases of myelomeningocele can be a devastating obstacle not only for patient but also for the patients family. Materials and methods: This was a descriptive study, started in January, 2007 and completed in December 2014 in the Department of Pediatric Surgery and Department of Neurosurgery of Dhaka Medical College & Hospital (DMCH).The medical records of 42 children with myelomeningocele operated at our center were reviewed retrospectively. The surgical & medical management protocol used for different sites of myelomeningocele was studied. Results: The age of most of the patients at the time of myelomeningocele repair was between 45 days to 60 days; however, children with ruptured myelomeningocele were consistently repaired early after controlling infection. In our study, 16 patients (38.1%) of myelomeningocele with hydrocephalus were operated for medium pressure ventriculoperitoneal (VP) shunt first, and then repair after 7 days to 10 days. VP shunt was done 7 days after repair of myelomeningocele in 11 patients (26.19%), who developed hydrocephalus postoperatively. All 8 patients with ruptured myelomeningocele (19.05%) were treated for ventriculitis first, then by repair. Seven patients (16.67%) with intact lesion were repaired between 4 weeks to 8 weeks of age. Complications including CSF leak, wound infection, wound dehiscence, paraplegia, autonomic incontinence, shunt infection and malfunction after repair of myelomeningocele occurred in 27 patients (64.29%). Six patients (14.29%) died during treatment protocol. All the patients were followed up postoperatively for 6 months to 1 year. Conclusion: Surgical intervention with or without VP shunt of patients with myelomeningocele produced good results. J. Paediatr. Surg. Bangladesh 5(2): 54-57, 2014 (July)